Timing of nitrogen application and cover crops on upland rice economic viability - Pascoaloto, Isabo Melina [UNESP] (2021)
The objective of this work was to evaluate the economic viability and competitiveness of upland rice (Oryza sativa), compared with flooded rice, in a system with different nitrogen fertilization timing and cover crops in Southeastern Brazil. The treatments consisted of upland rice grown under Urochloa brizantha or Urochloa ruziziensis straw, with the following fertilization: T, 30 kg ha(-1) N at rice sowing + no extra N supply (0 kg ha(-1)); C, 30 kg ha(-1) N at rice sowing + 90 kg ha(-1) N at rice tillering; A2, 30 kg ha(-1) N at rice sowing + 90 kg ha(-1) N one day before rice sowing; and A1, 30 kg ha(-1) N at rice sowing + 90 kg ha(-1) N in the living cover crops. Total operating cost, gross revenue, operating profit, profitability index, and equilibrium price were determined. Upland rice results in a monetary gain for the farmer similar to that of flooded rice when nitrogen is added, regardless of fertilization timing. Under rainfall deficit conditions, upland rice sown on U. brizantha straw shows higher profitability rates than when sown on U. ruziziensis. When there is a possibility of rainfall deficit, U. brizantha, as a cover plant, results in a greater economic security for upland rice producers.